Dipingere l’invisibile Da Klee agli artisti astratti, una ricerca per l’identità psichiatrica - Polese, Daniela (Il sogno della farfalla, 2013)
The passage to the twentieth century represented a real jump to something that had never existed before both in science and art. While medicine was revolutionised by X-rays and antibiotics, and physics found a new era with Einstein, Planck and Heisenberg, many artists explored what is not visible by retinal perception, creating a new art no longer interested in the description of reality. In psychiatry, in 1911, Bleuler coined the term schizophrenia, apparently thinking of a non-organic etiopathogenesis, but no progress was made regarding the knowledge of the human mind. Freud’s psychoanalysis made severe judgements about human nature and didn’t understand modern artists, as documentary evidence testifies. Why did psychiatry not change like medicine and other sciences? Do psychiatrists need artists to develop their identity? This paper focuses on the writings and paintings of Klee, Picasso, Kandinskij and the first abstract painters, in order to find a connection between the capacity of the artist and psychiatric and psychotherapeutic work. This could be necessary in order to really understand the patients beyond a mere description of their symptoms and start a coherent and therapeutic intervention.